Static vs. Dynamic Tutorials: Applying Usability Principles to Evaluate Online Point-of-Need Instruction. - Turner, Benjamin; Fuchs, Caroline; Todman, Anthony (Information Technology and Libraries, 2015)
This study had a two-fold purpose: to discover through the implementation of usability testing which mode of tutorial was more effective: screencasts containing audio/video directions (dynamic) or text-and-image tutorials (static); and to determine if online point-of-need tutorials were effective in helping undergraduate students use library resources. To this end, the authors conducted two rounds of usability tests consisting of three groups each, in which participants were asked to complete a database-searching task after viewing a text-and-image tutorial, audio/video tutorial, or no tutorial. The authors found that web usability testing was a useful tutorial-testing tool while discovering that participants learned most effectively from text-and-image tutorials, since both rounds of participants completed tasks more accurately and more quickly than those who received audio/video instruction or no instruction.